Factors Affecting the Risk Level of Mudharabah and Musyarakah Financing on the Profitability Level at BSI KCP Tanjung Balai - Alfathul Hisabi; Tuti Anggraini; Ahmad Perdana Indra (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The background of this research is that as is known, the main source of income at Bank Syariah Indonesia KCP Tanjung Balai comes from financing or fund distribution, if the financing provided is bad it will reduce the income or profitability that will be obtained by the bank. Banks must also pay attention to the distribution of funds to their customers as best as possible, because if the funds in the bank have not been distributed properly or the funds distributed by the bank are too large, it will likely affect the profitability or profits that will be obtained by the bank. In the financial reports published by the OJK and BI in 2021-2023, the NPF and FDR at BSI are increasing every year. A reasonable NPF should be a maximum of 5% and a maximum FDR of 85-100%, but the increase in NPF and FDR at BSI exceeds a reasonable value and this will likely affect the bank's profitability. The method used in this research is a quantitative method. The sample used was BSI KCP Tanjung Balai and was selected based on a purposive sampling method with observational data. Observations were conducted from 2021 to 2023. Data processing used the SPPS application and linear regression. The results of the study are from simultaneous testing (F test) with return on equity as the dependent variable also obtained a significance value of 0.000 or <0.05 which proves that factors from third party funds, financing to deposit ratio and non-performing financing simultaneously have a significant effect on return on equity (Profitability). This means that together third party funds, financing to deposit ratio and non-performing financing have a very high influence on the Risk Level of Mudharabah and Musyarakah Financing on the Level of Profitability at BSI KCP Tanjung Balai.